2020
DOI: 10.1007/s12264-019-00460-y
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Type 1 Receptors and Superoxide Anion Production in Hypothalamic Paraventricular Nucleus Contribute to Capsaicin-Induced Excitatory Renal Reflex and Sympathetic Activation

Abstract: Chemical stimulation of the kidney increases sympathetic activity and blood pressure in rats. The hypothalamic paraventricular nucleus (PVN) is important in mediating the excitatory renal reflex (ERR). In this study, we examined the role of molecular signaling in the PVN in mediating the capsaicin-induced ERR and sympathetic activation. Bilateral PVN microinjections were performed in rats under anesthesia. The ERR was elicited by infusion of capsaicin into the cortico-medullary border of the right kidney. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Capsaicin stimulates afferents and increases the afferent nerve activity at a low concentration, but causes denervation at a high concentration (Fitzgerald, 1983). The concentration of capsaicin in the present study was used to stimulate the renal afferents and cause ERR (Qiu et al, 2020;Ye et al, 2020;Zheng et al, 2020), which was much lower than the concentration used for denervation in previous studies (Fitzgerald, 1983;Foss et al, 2015). The capsaicin-induced ERR existed in the SHR at the ages of four, 12, and 24 weeks, indicating that the ERR is involved in the sympathetic activation and hypertension from the early stage to the sustained stage of hypertension in SHR.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Capsaicin stimulates afferents and increases the afferent nerve activity at a low concentration, but causes denervation at a high concentration (Fitzgerald, 1983). The concentration of capsaicin in the present study was used to stimulate the renal afferents and cause ERR (Qiu et al, 2020;Ye et al, 2020;Zheng et al, 2020), which was much lower than the concentration used for denervation in previous studies (Fitzgerald, 1983;Foss et al, 2015). The capsaicin-induced ERR existed in the SHR at the ages of four, 12, and 24 weeks, indicating that the ERR is involved in the sympathetic activation and hypertension from the early stage to the sustained stage of hypertension in SHR.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous study has shown that the renal infusion of capsaicin dose-dependently induces ERR in normal rats ( Ye et al, 2020 ). The dose of capsaicin at 1 nmol/min for 20 min was selected to induce ERR, and the vehicle for renal infusion had no significant effects on the RSNA, MAP, and HR ( Qiu et al, 2020 ; Ye et al, 2020 ; Zheng et al, 2020 ). At the age of 4 weeks, the early stage with slight or moderate hypertension, unilateral renal infusion of capsaicin caused immediate increases in the contralateral RSNA and MAP in both the WKY and SHR, lasting for at least 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations